The Infant Feeding Genogram: a tool for exploring family infant feeding history and identifying support needs. Issue 1 (December 2016) - Darwent, K.; McInnes, R.; Swanson, V.
Abstract Background Family culture and beliefs are passed through the generations within families and influence what constitutes appropriate infant care. This includes infant feeding decisions where a family history and support network congruent with women's infant feeding intentions has been shown to be important to women's breastfeeding experience. This is reflected in breastfeeding rates where women who were not breastfed themselves are less likely to initiate and continue with breastfeeding. Given the importance of family infant feeding history in the initiation and duration of breastfeeding, and the limited ability of some families to provide support; it is unclear why infant feeding family history and support networks are not explored during pregnancy. Methods The Infant Feeding Genogram was adapted from a simple pictorial device that is widely used in psychotherapy and genetic counselling. This tool was developed as part of a study investigating the experience of women when they were the first to breastfeed in their family. Fourteen Scottish participants completed their Infant Feeding Genogram as part of a semi-structured interview. The tool was adapted alongside their narratives to give a visual representation of each participant's family infant feeding history. Results The utility of the genogram is illustrated through two contrasting case examples with very different family feeding histories. The genogram showed family structures, patterns of infant feeding over time, and supportive or conflicting relationships. In the research setting it assisted women to explore their infant feeding history, identify challenges and sources of support and build rapport with the interviewer. Conclusions The infant feeding genogram is proposed as a time efficient tool that could assist health professionals and other breastfeeding workers to support women and their families and by stimulating discussion around breastfeeding, Bby identifying strengths or possible deficits in social support for each individual, the tool could inform tailored support and care interventions. The effectiveness and acceptability of the Infant Feeding Genogram requires testing in the clinical environment. However, its successful application in other clinical contexts, combined with the interest in genealogy in popular culture, mean this is likely to be an acceptable, family friendly way to develop more effective breastfeeding conversations.